PERLINDUNGAN HUKUM BAGI KONSUMEN MUSLIM DALAM MENGKONSUMSI MAKANAN PADA RESTORAN HOTEL YANG BELUM MEMILIKI SERTIFIKAT HALAL DI KOTA PEKANBARU - Putri, Yunda Agusti; Ismi, Hayatul; Firmanda, Hengki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In Pekanbaru, the population is predominantly Muslim, namely as many as 1,040,345 or 89.43%. This of course requires certainty regarding the food they eat, especially the food provided in hotel restaurants in Pekanbaru. The total Muslim population in Pekanbaru is 1,040,345 or 89.43%. In 2016, there were 30 hotel restaurants that did not have a halal certificate. In 2019 many hotel restaurants have halal certificates. Based on data obtained from BPJPH Pekanbaru, only 10 hotel restaurants have halal certification.This type of legal research is juridical sociological, which in this research, is carried out directly to the field to collect primary data, and uses descriptive methods. Meanwhile, if viewed from the nature of this research is descriptive.The results of this study are legal protection for Muslim consumers in consuming food at hotel restaurants that do not have a halal certificate in the city of Pekanbaru which is contained in Law Number 8 of 1999 concerning Consumer Protection, which only stipulates that business actors are prohibited from producing and / or trading goods and / or services that do not comply with the provisions of producing in a halal manner, as stated in the statement